2006
DOI: 10.1139/w06-040
|View full text |Cite
|
Sign up to set email alerts
|

In vitro susceptibility of isolates ofSporothrix schenckiito amphotericin B, itraconazole, and terbinafine: comparison of yeast and mycelial forms

Abstract: Forty-three clinical isolates of Sporothrix schenckii derived from humans and animals were evaluated in vitro for their susceptibility to amphotericin B, itraconazole, and terbinafine. MICs were determined by the method of micro dilution in liquid media, using protocols M27-A2 for the yeast form and M38-A for the mycelial form, both standardized by the Clinical Laboratory Standards Institute. In general, higher MICs were found for the mycelial form (intervals of up to two dilutions). In the case of amphoterici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
15
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 24 publications
6
15
0
1
Order By: Relevance
“…Regarding to the antifungal susceptibility profile of strains studied, our results were similar with those reported by other authors when testing S. schenckii in yeast phase. We obtained similar MIC values for terbinafine, posaconazole and fluconazole, while for amphotericin B, flucytosine, itraconazole, voriconazole and ketoconazole we observed greater discrepancies and extreme MIC values (two or more fold dilution).…”
Section: Discussionsupporting
confidence: 91%
“…Regarding to the antifungal susceptibility profile of strains studied, our results were similar with those reported by other authors when testing S. schenckii in yeast phase. We obtained similar MIC values for terbinafine, posaconazole and fluconazole, while for amphotericin B, flucytosine, itraconazole, voriconazole and ketoconazole we observed greater discrepancies and extreme MIC values (two or more fold dilution).…”
Section: Discussionsupporting
confidence: 91%
“…The results of this study conform to those of others showing the good susceptibility of S. schenckii to most of the antifungal agents apart form FLC and VRC 2,3,5,8–10 . In general, higher MIC values were found against the mycelial phase for all antifungal agents as demonstrated in other studies 8–10 .…”
Section: Discussionsupporting
confidence: 91%
“…Kohler et al. [10] suggested that one of the possibilities for the higher MIC values of mycelial phase could be because of inoculum size. However, a same size of the inoculum (10 5 ) was utilised by us for both phases.…”
Section: Discussionmentioning
confidence: 99%
“…For posaconazole, an agreement of 76.5% was found for mycelial and yeast forms, and only 47.6% was verified for voriconazole (87) in a study with Brazilian and Spanish S. schenckii strains. Another study found similar MICs for itraconazole and terbinafine, although the MIC of amphotericin B was slightly higher for mycelia (122). It has been also demonstrated that micafungin is more active against the mycelial than the yeast S. schenckii form (172).…”
Section: Antifungal Susceptibility Testsmentioning
confidence: 94%